Sonographic Finding of Persistent Renal Pelvic Wall Thickening in Children - Nai-Chia Fan; You-Lin Tain (Pediatrics and Neonatology)
Renal pelvic wall thickening (RPWT) is a sonographic finding, which is associated with urinary tract infection (UTI) and other genitourinary tract abnormalities. We aimed to determine the prevalence of RPWT and whether persistent RPWT related to vesicoureteral reflux (VUR). Materials and methods: We retrospectively reviewed sonographic findings of RPWT in children and adolescents referred for renal ultrasound study from January 2010 to December 2011. A total of 502 patients showing RPWT were included, 372 of whom received follow-up sonograms. Among them, 86 children underwent both follow-up sonograms and voiding cystourethrography studies. The association between persistent RPWT and VUR was analyzed. Results: A total of 602 sonograms with RPWT were identified, accounting for a prevalence of 11.4%. Follow-up sonograms, revealing that these patients had recovered from RPWT, was found in 93.7% (459/490) of renal units and in 92.7% (345/372) of the patients. Children with persistent RPWT had a strong association with VUR occurrence (p = 0.018) and high VUR grading (p = 0.006) compared to those without persistent RPWT. Conclusion: RPWT is a common finding in children and adolescents. Persistent RPWT is associated with VUR, especially with high grade VUR. Complementary uroradiological studies should be performed for children and adolescents with persistent RPWT.